2004
DOI: 10.1039/b406719n
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free Heck reactions using low Pd-loading

Abstract: as the base in methanol in a closed vessel (120 °C). 4 The original procedure reported by Heck is also ligand- Although P-ligands stabilise palladium and influence its catalytic activity, the simplest and cheapest Pd-catalysts are of course ligand-free systems, specifically when used in such low amounts that the term homeopathic is justified. Such an experimental protocol would constitute a significant advancement, especially if generally applicable. Recently, such ligand-free Heck reactions in organic solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
346
2
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(378 citation statements)
references
References 42 publications
25
346
2
5
Order By: Relevance
“…2 We feel this may not be a problem since we have demonstrated that Pd is not present in catalytically significant amounts in the organic phase. Another issue is the tendency of the Pd particles to aggregate.…”
Section: ð2þmentioning
confidence: 96%
See 1 more Smart Citation
“…2 We feel this may not be a problem since we have demonstrated that Pd is not present in catalytically significant amounts in the organic phase. Another issue is the tendency of the Pd particles to aggregate.…”
Section: ð2þmentioning
confidence: 96%
“…With the aim to generate and immobilize Pd-black in the third TOMAC phase, a suitable palladium precursor was sought, by testing PdCl 2 , Pd(OAc) 2 , Pd(PPh 3 ) 4 , and PdCl 2 (BzCN) 2 . Preliminary screening tests carried out with commercial A336 had indicated that Pd(PPh 3 ) 4 was the best precursor: it formed Pdblack which resided in the A336 phase.…”
mentioning
confidence: 99%
“…[88] Well-defined and in-situ-prepared Pd 0 nanoparticles in ionic liquids have been reported to promote CÀC coupling reactions such as Heck and Suzuki processes (Table 1, entries 6-9). In most cases, however, the Pd 0 nanoparticles are simple reservoirs of homogeneous Pd 0 catalytically active species akin to those observed with phosphane-free palladi- [89][90][91] such as simple Pd II compounds [92] or palladacycles. [93,94] It is highly probable that in these cases the Heck coupling reaction proceeds through the oxidative addition of the aryl halide on the nanoparticles surface, and the oxidized Pd species thus formed are detached from the surface and enter into the main catalytic cycle.…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…Metal nanoparticles, and in particular Pd-nanoparticles (also called 'Pd-colloids'), are stabilized by the presence-among others-of ammonium salts, [39][40][41][42][43] and surfactants, 44 by PEGs, 45 polysiloxane, 46 and by organic thiol monolayers. 47 The highly polar ethylene glycol was shown to be a catalystphilic phase earlier for SAPC.…”
Section: Peg Stabilized Metal Nanoparticlesmentioning
confidence: 99%